Influence of Coal Cleats on Conical Pick Cutting Process Based on PFC - Jinxia Liu; Chao Zhang; Fanchang Zeng; Wenting Liu (Advances in Materials Science and Engineering)
With the rising mining mechanized level, the conical pick is widely used in mining machines. The structure and mechanical properties of rocks and minerals are important factors affecting the cutting characteristics of the conical pick. In this paper, how the coal cleats affect the cutting process of shearers was researched, which will be of great significance to mining technology design. After analyzing the cutting process of conical pick and the test of coal mechanical properties, a group of coal cutting models of conical pick was established based on the empirical cutting parameters, various cleat spacing, simulation of mechanical performance of coal specimens, profile of conical pick, and SRM (synthetic rock mass) method in PFC (Particle Flow Code). Then, the simulations of the cutting process were carried out. The simulation results show that lump coal chips begin to form and fall off after the conical pick cuts to 50°; the cleats near the conical pick grow to be more obvious fractures; the mean and maximum fluctuations of cutting force increase with the increase of face and butt cleat spacing; the lower the density of cleat is, the more the cracks are formed during the cutting process; the face cleat spacing has greater influence on the service life of conical pick than the butt cleat spacing. This study more vividly reflects the influence of cleats on coal cutting process of the conical pick and plays a guiding role in design of mining technology.